The Great Ethiopian Renaissance Dam - Likelihood of Cooperation or Conflict between Ethiopia and Sudan? - Beyene, Embiale; Ali, Mohammed Seid (Ethiopian Journal of Social Sciences, 2018)
In this study, the existing challenges and prospect of the Ethio-Sudanese relations over the hydropolitics  of the Nile, particularly after the commencement of the Great Ethiopian Renaissance Dam (GERD) project, were critically examined. In addition, an attempt was made to examine whether the common water resource of the Nile might lead the two countries into conflict in the future. Within qualitative methodology, case study research design was employed. Major theories of hydro-politics were also critically reviewed to explain current relations and to predict likely future scenarios.   The analysis reveals that Egypt’s strong sphere of influence over the region has been one of the existential threats to the Ethio-Sudanese relation. Besides, the implications of the two parallel international legal regimes over the Nile water resource utilization during the colonial as well as the post-colonial periods have been existential challenges to the bilateral relations over the Nile question. However, rewarding practical lessons that Sudan has learnt from Ethiopia’s previous projects on the Nile River, has recently been creating an opportunity for an improvement of international relations. Finally, critical analysis of existential relations of the two neighboring states over the hydro-politics of the Nile also implies the recognition of cooperation over conflict as to the future prospect of their relationship. This is basically because of various forms of pragmatic hydro-diplomatic drives the two neighbors to settle existential and emerging challenges over the Nile water resource management.